Effect of Plant Densities on Growth and Yield of Cabbage - Janakan, L.; Sivachandiran, S.; Pradheeban, L. (Jaffna Science Association Annual Session – 2009, 2009)
Plant spacing is one of the important factors that determine productivity of vegetables crops. Jaffna farmers cultivate many local and exotic vegetables at different time period depending on their market demand. An experiment was conducted during July - December 2007 to study the effect of different plant densities on growth and yield components of Green cornet cabbage variety. The experiment was laid out in a Complete Randomized Design (CRD), with four replicates. Five treatments provided such as 60cm × 45cm, 50cm × 45cm, 50cm × 40cm, 50cm × 30cm and 45cm × 30cm in cabbage in calcic red yellow latasol soil. All other management practices were performed as per recommendation made by the Department of agriculture. Growth parameters and yield components were recorded. The results revealed that there was no significant different in growth parameters of cabbage. Anyhow, farmers can be advised to grow cabbage at 60cm × 45cm to obtain higher yield with better quality cabbage heads.